2020
DOI: 10.1111/ijcp.13799
|View full text |Cite
|
Sign up to set email alerts
|

Influence of intradialytic systolic blood pressure changes on arteriovenous access thrombosis in maintenance hemodialysis patients

Abstract: Background Arteriovenous access (AV) thrombosis is an important and preventable problem amongst chronic hemodialysis (HD) patients. Systolic blood pressure (SBP) fluctuation relates to higher cardiovascular mortality amongst these patients. We proposed there is a close relation between SBP changes and arteriovenous (AV) access thrombosis. We also determined other risk factors and biochemical parameters related to AV access failure. Methods 50 HD patients with thrombosis and 50 HD patients without thrombosis we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
(35 reference statements)
0
2
0
Order By: Relevance
“…For example, a secondary analysis of the Hemodialysis (HEMO) Study revealed frequent episodes of intradialytic hypotension associated with AV fistula thrombosis. Two recent retrospective studies also found that the variability of intradialytic BP can predict access thrombosis ( 13 , 14 ). Nonetheless, in most circumstances, access thrombosis occurred in the inter-dialytic period.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…For example, a secondary analysis of the Hemodialysis (HEMO) Study revealed frequent episodes of intradialytic hypotension associated with AV fistula thrombosis. Two recent retrospective studies also found that the variability of intradialytic BP can predict access thrombosis ( 13 , 14 ). Nonetheless, in most circumstances, access thrombosis occurred in the inter-dialytic period.…”
Section: Discussionmentioning
confidence: 97%
“…The effect of short-term BPV on the prognosis of hemodialysis patients has been reported. Intradialytic hypotension and intradialytic BP variability were associated with vascular access outcomes ( 6 , 13 , 14 ). Long-term BPV is reproducible over time but is only modestly related to short-term variability ( 15 , 16 ).…”
Section: Introductionmentioning
confidence: 99%